New search directions of conjugate gradient methods for unconstrained nonlinear optimization - OUAOUA , Mohamed Lamine; KHELLADI , Samia Supervisor; BENTERKI , Djamel Co- Supervisor (Setif 1 University - Ferhat ABBAS , Faculty of Sciences, 2026)
This thesis deals with solving the unconstrained nonlinear problems using conjugate gradient methods, where we proposed two new types of these methods. We established the descent condition for the search directions, and we proved the global convergence of the proposed algorithms under the strong Wolfe line search. The obtained results were further supported by various numerical experiments with large dimensions
تتناول هذه الأطروحة حل مسائل الأمثلة غير الخطية وغير المقيدة باستخدام طرق التدرج المترافق، حيث أقترحنا طريقتين جديدتين للتدرج المترافق، وقد قمنا بإثبات شرط التناقص بالنسبة لإتجاهات البحث، والتقارب الإجمالي للخوارزميات المقترحة. كما تم تعزيز النتائج المحصل عليها من خلال تجارب عددية مختلفة أثبتت تفوق الطرق المقترحة مقارنة مع طرق أخرى
Keywords: Unconstrained nonlinear optimization; Conjugate gradient method; Descent direction; Inexact line search; Global convergence